Alteration in secondary metabolites in Lasioptera sp. (Diptera, Cecidomyiidae) induced galled and ungalled leaves of Glycosmis pentaphylla (Retz.) DC. - Haridas , Keerthana; Nasser, M. (ENTOMON, 2026)
Glycosmis pentaphylla (Retz.) DC. (Rutaceae) is an ethnobotanically important medicinal plant. On this host, cylindrical- green epiphyllous galls are induced on the leaves by Lasioptera sp. (Diptera, Cecidomyiidae). In the present study, the changes in concentration of major secondary metabolites during the development of insect-induced plant galls in G. pentaphylla analysed and the results show that gall tissues contained significantly higher concentrations of tannins, phenols, and alkaloids, but lower concentrations of flavonoids, compared with ungalled leaves. These gall-associated alterations in secondary metabolite profiles may represent host defense responses initiated by gall induction and reflect the complex biochemical interactions between the gall inducer Lasioptera sp. and the host plant.